Trajetórias de formação e atuação de acupunturistas - Nunes, Marcelo Felipe (Universidade do Vale do Rio dos Sinos, 2013)
The objective of the article was to analyze the trajectories of formation and action of acupuncturists. This is a qualitative study, based on the methodological framework of the narratives of life stories. There were eight participants among healthcare professionals, five men and three women, graduated in nursing, physiotherapy and medicine, who used acupuncture from the perspective of Traditional Chinese Medicine (TCM) and answered structured interviews. The analysis of the narratives implied three main categories: Search for new rationalities in health; Entering the complex world of acupuncture, Acupuncture goes beyond the needle. It became evident that the search for acupuncture was motivated by dissatisfaction with the initial training into biomedical paradigm. The trajectory of the education in acupuncture was gradual and involved a deep insertion into the rationality of TCM, due to the complexity of its treatment plan, which led the participants to realize that the needle insertion represents the confluence of several aspects of TCM, which can not be reduced to mere application of a needling technique. In this regard, it appoints the need of rethinking the education of the healthcare professionals, as well as to investigate the actions of those who work for the Sistema Único de Saúde.
Acupuncture goes beyond the needle: trajectories of formation and action of acupuncturists
Keywords: Acupuntura; Medicina tradicional chinesa; Trajetória profissional; Narrativas; Acupuncture; Traditional chinese medicine; Professional trajectory; Narration; ACCNPQ::Ciências da Saúde::Saúde Coletiva